Pedagogical Political Project: A systematic review (Research, Society and Development, 2022)
The document entitled Pedagogical Political Project is considered one of the main resources for the conduct of democratic management and aligned with the factual needs of each school. This research aimed to conduct a systematic review of the literature to access studies on the subject in contemporary times. For this, a survey was carried out in the databases: CAPES, OASIS BR, PBi in the period from 2017 to 2022. Studies that have as descriptors "Political Pedagogical Project and School Management", published in Portuguese, Spanish and English. Of the 57 articles identified, after initial exclusions, 16 were classified for full reading and the same 16 for qualitative analysis. It was seen that there are still few studies that deepen the theme of the Pedagogical Political Project, and most of them do not focus on the role of the school principal, who is most responsible for conducting this project.